Penerapan Kode Etik terhadap Profesi Akuntan di Indonesia - Eka Bima Safitri; Anggita Riski Dwi Lestari; Suryardin Gee; Yeni A Tumanggor; Ayu Diah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to find out the code of ethics in the accounting profession in Indonesia, consisting of the influence of the code of ethics and the application of the code of ethics on the accounting profession in Indonesia. This study uses the Systematic Literature Review (SLR) method. SLR is a research technique that is carried out to evaluate, analyze, collect and maintain information from several article sources obtained from websites such as google scholar as many as 30 articles. The result of this study is that a code of ethics is very necessary in the accounting profession, especially in Indonesia. Based on the influence of the code of ethics in Indonesia, it increases public trust and regulates behavior professionally. And based on the application of the code of ethics, the Indonesian accountant profession can prevent unethical practices and abuse of office as well as strengthen accountability and transparency.